2014
DOI: 10.12980/apjtb.4.2014c55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on changes in cognitive performances and brain malondialdehyde concentration induced by sub–chronic co–administration of chlorpyrifos and cypermethrin in male Wister rats

Abstract: Cognitive deficits elicited by CPF and CYP was mitigated by melatonin due to its antioxidant property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…During the past few years, the functional role of melatonin in improving cognitive function has been reported . A variety of studies have demonstrated that melatonin can ameliorate cognitive impairment caused by total sleep deprivation, pesticide exposure, diabetes mellitus, and even irradiation injury . Electrophysiological studies also suggest that melatonin is a potent regulator involved in the processes of memory formation, LTP, synaptic transmission, and neuronal plasticity in the hippocampus and other brain regions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few years, the functional role of melatonin in improving cognitive function has been reported . A variety of studies have demonstrated that melatonin can ameliorate cognitive impairment caused by total sleep deprivation, pesticide exposure, diabetes mellitus, and even irradiation injury . Electrophysiological studies also suggest that melatonin is a potent regulator involved in the processes of memory formation, LTP, synaptic transmission, and neuronal plasticity in the hippocampus and other brain regions .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 A variety of studies have demonstrated that melatonin can ameliorate cognitive impairment caused by total sleep deprivation, pesticide exposure, diabetes mellitus, and even irradiation injury. [19][20][21][22] Electrophysiological studies also suggest that melatonin is a potent regulator involved in the processes of memory formation, LTP, synaptic transmission, and neuronal plasticity in the hippocampus and other brain regions. [23][24][25][26] Melatonin can have neuro-protective effects on cognitive function by depressing oxidative stress and activating the molecular machinery related to oxidative modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Male rats exposed to sipermetrin in different doses have increased malondialdehyde (MDA) content in the brain, heart, liver, kidneys and testes. 22 A study by Banke et al (2014) showed that MDA concentrations in the brain increased after exposure to a mixture of sipermethrin and clorfirifos for 12 weeks. 23 Malondialdehyde (MDA) is a lipid peroxidation product resulting from the reaction of oxygen radicals with polyunsaturated fatty acid residues in phospholipid membrane, and shows the presence of protein and DNA damage.…”
Section: Effect Of 17-estradiol Level On Uterine Mda Levelmentioning
confidence: 99%
“…22 A study by Banke et al (2014) showed that MDA concentrations in the brain increased after exposure to a mixture of sipermethrin and clorfirifos for 12 weeks. 23 Malondialdehyde (MDA) is a lipid peroxidation product resulting from the reaction of oxygen radicals with polyunsaturated fatty acid residues in phospholipid membrane, and shows the presence of protein and DNA damage. 23 The main source of MDA in biological samples is the peroxidation of polyunsaturated fatty acids with two or more methylene double binds.…”
Section: Effect Of 17-estradiol Level On Uterine Mda Levelmentioning
confidence: 99%
“…Consequently, the combination of these chemicals exhibits a different toxicological profile compared with toxicity of the pesticides singly (Babu et al, 2010). Although combination of pesticides is beneficial in combating pest resistance, this combination poses a new challenge since the resultant effects of such interactions are unknown (Banke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%